Improving optical properties of remote phosphor LED using green Y2O3:Ho3+ and red Mg4(F)(Ge, Sn)O6:Mn2+ layers - My Hanh Nguyen Thi; Nguyen Thi Phuong Loan; Nguyen Doan Quoc Anh (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
The lighting device that employs diodes to create white light (WLEDs) with quantum dots (QDs) and phosphor layers is a promising lighting method that is increasingly used in many fields on account of the remarkable color expressing ability. The QDs film is usually placed apart from the phosphor layer according to the packaging configuration to prevent light loss due to backscattering as well as preserve the consistency of the ligands on the QDs surface. The article also conducted experiments to compare the lighting properties and thermal output of the two packaging orders of QDs and phosphor. The heat discharing ranges were simulated with thermography technology, moreover, other parameters such as light energy emission and PL spectra are acquired to evaluate the efficiency of the packaging order. The results from the practical experiment show that while under 10% wt., the luminous output (LO) of green QDs-on-phosphor structure reaches 1130 lm, higher than the red QDs-on-phosphor structure with 878 lm, and the color rendering value in the configuration with red QDs on phosphor is Ra = 74 are higher than Ra = 68 index of the green QDs-on-phosphor structure. As a result, the QDs-on-phosphor is determined as the better packaging configuration to choose to achieve an overall improvement in lighting efficiency, color rendering index